My darling, my hamburger : a novel - Zindel, Paul. (New York : Bantam, 1971)
Four high school seniors struggle with the responsibilities of growing up, particularly the problems of an intimate relationship.
New York Times.
Wilson's Junior High School.
5.9
7-9
Young Adult
Keywords: Youth -- Fiction; Youth -- Fiction